Trichoderma The Most Widely Used Fungicide - Manjur Shah, Mohammad; Sharif, Umar; Rufai Buhari, Tijjani (IntechOpen, 2019)
Trichoderma is a genus of fungi that are present in all soils, where they are the most prevalent culturable fungi. They are also the most successful biofungicides used in today's agriculture. These green-colored fungi are well known for their antifungal and plant-growth-stimulating effects. This book provides comprehensive information on Trichoderma and its use in medical, agricultural and industrial applications. Section I focuses mainly on identification of Trichoderma species, and Section II is concerned with Trichoderma as a biological control agent. Chapters in these sections cover topics ranging from taxonomic status and biodiversity to biochemical analysis and bio-control application.